Daily Ups and Downs: An Event-Sampling Study of the Mediated Moderation of Prosocial Engagement on Well-Being. Issue 6 (August 2018) - Hui, Bryant P. H.; Kogan, Aleksandr
Numerous studies have shown that acting prosocially promotes the altruist's well-being. What has been less clear, however, is when the effect is the strongest and what mechanism is behind the well-being benefits of prosocial action. We asked a community sample ( N = 383) to record their prosocial engagement, well-being levels, and autonomy, relatedness, and competence 4 times daily for 2 weeks using an app-based event-sampling method. We found that only one's competence—and neither autonomy nor relatedness—at one time point ( t − 1) moderated the effect of prosocial engagement on hedonic and eudaimonic well-being at a subsequent time point ( t ). Specifically, when participants reported lower competence levels at t − 1, the relationship between acting prosocially and well-being was stronger at t . We further demonstrated that this interaction was mediated by competence levels at t .